Characteristics of patients with suspected COVID-19 infection and the outcome of a visit to a Covid-outpatient clinic (General Practice, 2025)
Introduction. The COVID-19 patients were treated inoutpatient clinics at primary healthcare centers, which alleviatedthe pressure on secondary and tertiary healthcare levels.Objective. We aimed to research the characteristics ofCOVID patients, such as their symptoms, test results, comorbidities,and exam outcomes.Method. We completed a questionnaire for patientswho attended for examination between April 23 and April 29,2021. We collected data on gender, age, symptoms, comorbidities,vaccination status, and examination outcomes. Thedata were statistically analyzed using the SPSS program.Results. A total of 222 participants, comprising 61.7%women, were involved in the study, with an average age of47.9 ± 15.2 years. Among them, 24.8% were vaccinated, and60.4% tested positive for COVID-19. The most commonsymptoms reported included malaise, muscle and joint pain,cough, and fever. Approximately half of the participants hadcomorbidities, primarily among older individuals. Statisticalanalysis showed no significant correlation between COVID-19 test results and vaccination status (p=0.099), nor wasthere a significant relationship with the presence of comorbidities(p=0.118). Patients exhibiting milder symptoms weretypically sent home, while 26.1% were referred for furtherdiagnostic testing, and 10.4% were admitted to the hospital.Vaccination status did not appear to influence the outcomeof the visits (p=0.240). Participants aged 51 to 65 were mostfrequently referred for further diagnostics, while those over65 (p=0.004) and individuals with comorbidities (p=0.003)were more likely to be hospitalized.Conclusion. There was no significant difference inpositive COVID-19 test results regarding vaccination andcomorbidities. Only 10% of the patients were referred to thehospital, primarily those over 65 and patients with comorbidities.
Keywords: COVID-19 symptoms; comorbidities; COVID- 19 testing; vaccination status; COVID outpatient clinics; hospital referral